CAOS—Episodic Cerebellar Ataxia, Areflexia, Optic Atrophy, and Sensorineural Hearing Loss: A Third Allelic Disorder of the ATP1A3 Gene. (November 2015) - Heimer, Gali; Sadaka, Yair; Israelian, Lori; Feiglin, Ariel; Ruggieri, Alessandra; Marshall, Christian R.; Scherer, Stephen W.; Ganelin-Cohen, Esther; Marek-Yagel, Dina; Tzadok, Michal; Nissenkorn, Andreea; Anikster, Yair; et al.
We describe the molecular basis of a distinctive syndrome characterized by infantile stress-induced episodic weakness, ataxia, and sensorineural hearing loss, with permanent areflexia and optic nerve pallor. Whole exome sequencing identified a deleterious heterozygous c.2452 G>A, p.(E818K) variant in the ATP1A3 gene and structural analysis predicted its protein-destabilizing effect. This variant has not been reported in context with rapid-onset dystonia parkinsonism and alternating hemiplegia of childhood, the 2 main diseases associated with ATP1A3 . The clinical presentation in the family described here differs categorically from these diseases in age of onset, clinical course, cerebellar over extrapyramidal movement disorder predominance, and peripheral nervous system involvement. While this paper was in review, a highly resembling phenotype was reported in additional patients carrying the same c.2452 G>A variant. Our findings substantiate this variant as the cause of a unique inherited autosomal dominant neurologic syndrome that constitutes a third allelic disease of the ATP1A3 gene.